Fiscal Policy Spillovers in the Euro Area – A New Assessment - António Afonso; Daniel Loureiro (CESifo GmbH, 2024)
We compute a GVAR to estimate the fiscal spillovers on output, consumption, investment, employment, and income, from 2002Q1 to 2021Q4, with 16 Euro Area (EA) countries. We found that a budget balance expansionary shock in Germany would generate positive spillovers on output and employment. Negative cross-country effects on consumption were also found. No significant spillovers on investment or income were observed following this shock. Greater and more significant spillovers were found after an EA global shock. There are also positive effects on private investment. However, a global shock still does not generate significant effects on income and increases the magnitude of the negative short-run spillovers on consumption. Greece is one of the countries more affected by short-run negative spillovers. Finally, national and global fiscal shocks put upward pressure on prices and generate negative effects on public debt. From a policy perspective, we recommend the reinforcement of the fiscal coordination framework.
Keywords: C32; E62; F42; F45; 330; Euro Area; fiscal spillovers; policy coordination; GVAR